If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + 15x = -9y Solving 27 + 15x = -9y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 15x = -27 + -9y Combine like terms: 27 + -27 = 0 0 + 15x = -27 + -9y 15x = -27 + -9y Divide each side by '15'. x = -1.8 + -0.6y Simplifying x = -1.8 + -0.6y
| 14-n=-14 | | (7p+13)=(3p+37) | | 10(b+2)-4(2b+8)= | | -6-2x=4 | | C=2t+3 | | w+6w=11 | | 2m-n=-14 | | 59*3= | | 8c+3=-3 | | 1.8x=3.6 | | 4.5x=67.9 | | -7m+6n=59 | | (x-9)*(6x+15)= | | 3(3n-2)=(2n+2)+9 | | 20x=25x+25 | | 8x-12=7x+4 | | -4x-4=-44 | | (-5-(-64))= | | 4x-16=35 | | 3b=ab-8 | | 6x+2/2=19 | | Y^4=4096 | | 13=2c+3*5c | | x+y=1040 | | 3x-5(3x-12)=-24 | | 2g-8g= | | .005x-.003=.01 | | -16+6y+6y=-8 | | .20(2x-3)=7 | | -16+6y+67=-8 | | s+10=20 | | (152+7x)+(6x-10)= |